Penyuluhan Dan Pelatihan Pembuatan Pestisida Bioinsektisida Ramah Lingkungan - Joko Sri Mulyono; Sri Purwanti; Megawati Citra Alam; Yuni Rosita Dewi; Dimas Ganda Permana Putra; Khoirul Anam; Bintang Pramudana Widi; Shofiatul Ajkiyah (Lembaga Pengembangan Kinerja Dosen, 2023)
Reducing the amount of chemical pesticides that can be used without causing adverse effects is the goal of this bioinsecticide. plant protection products that specifically describe pesticides used in agriculture to differentiate them from other products. Pests are a problem for local residents associated with agriculture. Plant pests that often appear are detrimental to farmers' crops, especially rice. At the village hall and in the rice fields, residents, instructors and students enthusiastically listened to explanations or materials as well as direct practice. The aim is to provide information and educate the public through counseling and training in making environmentally friendly bioinsecticide pesticides in Tinggar Buntut Village by lecturers at the agriculture faculty, Mayjen Sungkono University. by applying collaborative cooperation methods. The Faculty of Agriculture can designate Tinggarbuntut Village as a target village. using an experimental quantitative approach method with pre test post-test one group design to see the increase in knowledge after counseling and training